MAPPING OF ANGEL SITES: : Optimization Of Folklore In Field Of Tourism In East Java - Indrawan, Aditya; Dias Alvy Pratama; M Ubaidillah Faqih (The Indonesian Journal of Social Studies, 2025)
Indonesia has abundant natural and cultural potential. This potential can be used as a selling point in the field of tourism, but further development of culture-based tourism is needed. Folklore is one of the cultures that exists in Indonesia. This article discusses the mapping of several fairy-based tourism sites and how the narrative of fairies in East Java can be optimally used in tourism activities. This study uses a qualitative research method with a multi-location approach. The multi-location approach is used to find more accurate data because there are more than one tourist attractions in East Java that are identical to the fairy narrative. Based on the research results, it was found that fairy narratives are not only used for promoting tourist destinations but also for preserving the surrounding nature. This is reflected in several prohibitions found in some tourist destinations. These prohibitions are conveyed by several local residents living around the tourist destinations. Indirectly, these various prohibitions aim to preserve nature